Trust: an essential condition in the application of a caregiver support intervention in nursing practice - Zegwaard, Marian I. (BMC Psychiatry, 2017)
BACKGROUND: The recent policy of deinstitutionalization of health care in Western countries has resulted in a growing number of people - including elderly - with severe mental illness living in the community where they rely on families and others for support in daily living. Caregiving for partners, parents, children, and significant others can be a stressful experience and has been associated with psychosocial problems and poorer physical health. To support caregivers, a new, complex, nurse-led caregiver - centered intervention was developed. The intervention focuses on preventing deterioration in the wellbeing of caregivers. The objective of this study is to obtain a better understanding of the potentials of this new intervention. METHODS: We applied an interpretative qualitative field study at two Dutch mental health care institutes. Thirteen caregivers participated in a one-time semi-structured interview. RESULTS: From the caregivers’ perspective, a trusting relationship between caregivers and the mental health nurse is an essential condition for the depth and hence the effectiveness of the caregiver-centered counseling intervention. In this trusting relationship three overlapping and mutually reinforcing phases were identified (1) phase of engagement, (2) recognition of personal needs and (3) hope and optimism. Each phase encompasses key experiences that enhanced trust in that phase. CONCLUSIONS: Collaborative relationships between caregivers and mental health nurses provide a framework in which the mental health nurse can assess and help not only patients but also caregivers to gain insight into their situation and take on new roles and responsibilities in ways that promote their wellbeing. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-017-1209-2) contains supplementary material, which is available to authorized users.